Kritik Islam Progresif terhadap Formalisasi Agama: Studi Pemikiran Farish A. Noor - Nur Sidik (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This article examines Farish A. Noor's progressive Islamic thought as a critique of the formalization and bureaucratization of religion in the socio-political context of Southeast Asia. Islam is understood not merely as a normative institution, but as a system of ethical and humanistic values with an emancipatory function. This research uses a qualitative approach through thought analysis to explore the intellectual background, socio-political context, and characteristics of Farish A. Noor's progressive Islamic ideas. The results indicate that his thoughts emerged as a response to state domination over religion, religious conservatism, and the hegemony of official interpretations that undermine critical thinking among the people. Through reinterpreting the concept of